2022
DOI: 10.1002/lio2.962
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide may improve pharyngocutaneous fistula healing through downregulation of cystatins: A pilot study

Abstract: Background: Pharyngocutaneous fistula (PCF) and salivary leaks are well known complications of head and neck surgery. The medical management of PCF has included the use of octreotide without a well-defined understanding of its therapeutic mechanism. We hypothesized that octreotide induces alterations in the saliva proteome and that these alterations may provide insight into the mechanism of action underlying improved PCF healing. We undertook an exploratory pilot study in healthy controls that involved collect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…PCF develops as a result of failure of pharyngeal repair and consists of a communication between the pharynx and the cervical skin or the tracheal stoma at the site of the surgical incision 22,23 . An increasing amount of research attention is now focused on not only early detection and prevention of PCF but also more effective treatments 20,24,25 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…PCF develops as a result of failure of pharyngeal repair and consists of a communication between the pharynx and the cervical skin or the tracheal stoma at the site of the surgical incision 22,23 . An increasing amount of research attention is now focused on not only early detection and prevention of PCF but also more effective treatments 20,24,25 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, investigators are aiming to develop novel treatment strategies that could accelerate healing of PCF 28 . Cohen et al reported that octreotide‐induced downregulation of cystatins could improve healing of PCF by promoting an angiogenic response as well as proliferation and migration of cells 24 . Rani et al also showed that hyperbaric oxygen therapy could be helpful for patients with PCF who have failed conservative treatment 30 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations